Positive effects of amphiregulin on human oocyte maturation and its molecular drivers in patients with polycystic ovary syndrome. Issue 1 (6th November 2021) - Akin, Nazli; Le, Anh H; Ha, Uyen D T; Romero, Sergio; Sanchez, Flor; Pham, Toan D; Nguyen, Minh H N; Anckaert, Ellen; Ho, Tuong M; Smitz, Johan; Vuong, Lan N
Abstract: STUDY QUESTION: Does use of medium containing amphiregulin improve meiotic maturation efficiency in oocytes of women with polycystic ovary syndrome (PCOS) undergoing in vitro maturation (IVM) preceded by a capacitation culture step capacitation IVM (CAPA-IVM)? SUMMARY ANSWER: Use of medium containing amphiregulin significantly increased the maturation rate from oocytes retrieved from follicles with diameters <6 or ≥6 mm pre-cultured in capacitation medium. WHAT IS KNOWN ALREADY: Amphiregulin concentration in follicular fluid is correlated with human oocyte developmental competence. Amphiregulin added to the meiotic trigger has been shown to improve outcomes of IVM in a range of mammalian species. STUDY DESIGN, SIZE, DURATION: This prospective, randomized cohort study included 30 patients and was conducted at an academic infertility centre in Vietnam from April to December 2019. Patients with PCOS were included. PARTICIPANTS/MATERIALS, SETTING, METHODS: In the first stage, sibling oocytes from each patient (671 in total) were allocated in equal numbers to maturation in medium with (CAPA-AREG) or without (CAPA-Control) amphiregulin 100 ng/ml. After a maturation check and fertilization using intracytoplasmic sperm injection (ICSI), all good quality Day 3 embryos were vitrified. Cumulus cells (CCs) from both groups were collected at the moment of ICSI denudation and underwent a molecular analysis to quantify key transcripts of oocyte maturation and to relate these to early embryo development. On return for frozen embryo transfer (second stage), patients were randomized to have either CAPA-AREG or CAPA-Control embryo(s) implanted. Where no embryo(s) from the randomized group were available, embryo(s) from the other group were transferred. The primary endpoint of the study was meiotic maturation efficiency (proportion of metaphase II [MII] oocytes; maturation rate). MAIN RESULTS AND THE ROLE OF CHANCE: In the per-patient analysis, the number of MII oocytes was significantly higher in the CAPA-AREG group versus the CAPA-Control group (median [interquartile range] 7.0 [5.3, 8.0] versus 6.0 [4.0, 7.0]; P = 0.01). When each oocyte was evaluated, the maturation rate was also significantly higher in the CAPA-AREG group versus the CAPA-Control group (67.6% versus 55.2%; relative risk [RR] 1.22 [95% confidence interval (CI) 1.08–1.38]; P = 0.001). No other IVM or embryology outcomes differed significantly between the two groups. Rates of clinical pregnancy (66.7% versus 42.9%; RR 1.56 [95% CI 0.77–3.14]), ongoing pregnancy (53.3% versus 28.6%; RR 1.87 [95% CI 0.72–4.85]) and live birth (46.7% versus 28.6%; RR 1.63 [95% CI 0.61–4.39]) were numerically higher in the patients who had CAPA-AREG versus CAPA-Control embryos implanted, but each fertility and obstetric outcome did not differ significantly between the groups. In the CAPA-AREG group, there were significant shifts in CC expression of genes involved in steroidogenesis ( STAR, 3BHSD ), the ovulatory cascade ( DUSP16, EGFR, HAS2, PTGR2, PTGS2, RPS6KA2 ), redox and glucose metabolism ( CAT, GPX1, SOD2, SLC2A1, LDHA ) and transcription ( NRF2 ). The expression of three genes ( TRPM7, VCAN and JUN ) in CCs showed a significant correlation with embryo quality. LIMITATIONS, REASONS FOR CAUTION: This study included only Vietnamese women with PCOS, limiting the generalizability. Although 100 ng/ml amphiregulin addition to the maturation culture step significantly improved the MII rate, the sample size in this study was small, meaning that these findings should be considered as exploratory. Therefore, a larger patient cohort is needed to confirm whether the positive effects of amphiregulin translate into improved fertility outcomes in patients undergoing IVM. WIDER IMPLICATIONS OF THE FINDINGS: Data from this study confirm the beneficial effects of amphiregulin during IVM with respect to the trigger of oocyte maturation. The gene expression findings in cumulus indicate that multiple pathways might contribute to these beneficial effects and confirm the key role of the epidermal growth factor system in the stepwise acquisition of human oocyte competence. STUDY FUNDING/COMPETING INTEREST(S): This work was funded by the Vietnam National Foundation for Science and Technology Development (NAFOSTED; grant number FWO.106-YS.2017.02) and by the Fund for Research Flanders (FWO; grant number G.OD97.18N). L.N.V. has received speaker and conference fees from Merck, grants, speaker and conference fees from Merck Sharpe and Dohme, and speaker, conference and scientific board fees from Ferring. T.M.H. has received speaker fees from Merck, Merck Sharp and Dohme and Ferring. J.S. reports speaker fees from Ferring Pharmaceuticals and Biomérieux Diagnostics and grants from FWO Flanders, is co-inventor on granted patents on CAPA-IVM methodologies in USA (US10392601B2), Europe (EP3234112B1) and Japan (JP 6806683 registered 08-12-2020) and is a co-shareholder of Lavima Fertility Inc., a spin-off company of the Vrije Universiteit Brussel (VUB, Brussels, Belgium). NA, TDP, AHL, MNHN, SR, FS, EA and UDTH report no financial relationships with any organizations that might have an interest in the submitted work in the previous three years, and no other relationships or activities that could appear to have influenced the submitted work. TRIAL REGISTRATION NUMBER: NCT03915054.